FAKTOR YANG MEMPENGARUHI FIRM PERFORMANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - hastuti, rini tri (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2018)
The purpose of this empirical research is to examine the effect of leverage, firm size, and environmental performance on firm performance on manufacturing companies listed on the Indonesia Stock Exchange from 2014-2016. This research used 31 manufacturing companies that were selected using purposive sampling method for a total of 146 data in three years. The data used in this research are secondary data in the form of financial statements. Before testing the hypothesis, we did the classical assumptions test. Therefore, the statistical method used to test the hypothesis is the multiple linear regression model. The results showed that the leverage and environmental performance have a significant effect on firm performance, while firm size do not have a significant effect on firm performance. Keywords: Leverage, Firm size, Environmental performance, Firm performance.